PENGATURAN MENGENAI HARGA SAHAM WAJAR SEBAGAI BENTUK PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM PUBLIK DALAM MERGER BANK YANG BERBENTUK PERSEROAN TERBUKA - Pande Yogantara S. (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Banking crisis that occurred in 1997 and the issuance of Bank Indonesia regulations Number 8/16/PBI/2006 Regarding Single Presence on Indonesian Banking, led to a merger in the banking industry. Merger action is a legal act, not only causes economic and financial consequences but also the juridical consequences. The consequences of the merger to be seen is the impact on the public shareholders especially in the of bank in form public company.In the event of a merger, position of public shareholders is very weak in regard to corporate decision-making (the company). If the views of the ownership of shares, public shareholders are almost always going to lose when dealing with shareholders, because for every share issued has one vote. The results of this research showedCapital Markets Law and BAPEPAM regulation Number IX.G.1 About Merger or Consolidation Enterprises Public Company or the Issuerdoes not regulate further the understanding and clear criteria of "reasonable stock price". But in bank merger the form of public company,necessary services as a professional independent appraisal supporting the capital markets as mentioned in Article 64 and Article 67 of Act Number 8 Year 1995 About Capital Market,which in turn can make a reasonable assessment of the stock price that reflects fairness for public or minority shareholders.